Lauric Acid-Modified Nitraria Seed Meal Composite as Green Carrier Material for Pesticide Controlled Release - Bo Bai; Xiaohui Xu; Jingjie Hai; Na Hu; Honglun Wang; Yourui Suo (Journal of Chemistry)
To alleviate the adverse effects of pesticide residues on the environment, development of a more safe, economical, and reliable usage approach of pesticides is critically urgent. In the present study, a novel pesticide carrier LA-NSM (lauric acid-modified Nitraria seed meal) with controlled release property was prepared through grafting esterification of lauric acid onto Nitraria seed meal substrates. The structure of the obtained samples was characterized by Fourier-transform infrared spectroscopy, scanning electron microscopy, and contact angle measurements. The results indicated that LA-NSM products had a well-defined hydrophobic surface and irregular holes for efficient loading of pesticide molecules. Deltamethrin (DEL), a representative insoluble pyrethroid insecticide in water, was deliberately selected as the index pesticide to evaluate the loading and releasing efficiency of LA-NSM. The loading capacity of LA-NSM for DEL can reach about 1068 mg/g. pH, humidity of soil, and temperature had a significant influence on controlled release performance of LA-NSM@DEL. Moreover, the releasing kinetics of LA-NSM@DEL composites could be fitted well with the Higuchi model. Overall, the highly hydrophobic property, excellent loading, and controlled release ability of LA-NSM made it a promising candidate in agricultural applications.